1996
DOI: 10.1093/bja/76.5.731
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethylstarch compared with modified gelatin as volume preload before spinal anaesthesia for Caesarean section

Abstract: We studied 90 patients undergoing elective Caesarean section under spinal anaesthesia who received lactated Ringer's solution 1000 ml with up to 1000 ml of modified gelatin, lactated Ringer's solution 1000 ml with up to 1000 ml of 6% hydroxyethylstarch or only up to 1000 ml of 6% hydroxyethylstarch. Lumbar puncture was performed as soon as 500 ml of the colloid were infused. The incidence of hypotension, number of patients requiring a vasopressor and doses of ephedrine required to restore arterial pressure wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 7 publications
4
28
0
1
Order By: Relevance
“…23 In the present study also, it has been shown that prophylactic ephedrine is more effective for preventing hypotension in healthy parturient undergoing spinal anaesthesia for caesarean section. Critchley et al observed significant increase in heart rate in the ephedrine treated group, which is similar to our findings in the combination group-Group C and Group D. Reducing the dose of vasopressor in the combination group, could obviate this problem.…”
Section: Resultssupporting
confidence: 65%
“…23 In the present study also, it has been shown that prophylactic ephedrine is more effective for preventing hypotension in healthy parturient undergoing spinal anaesthesia for caesarean section. Critchley et al observed significant increase in heart rate in the ephedrine treated group, which is similar to our findings in the combination group-Group C and Group D. Reducing the dose of vasopressor in the combination group, could obviate this problem.…”
Section: Resultssupporting
confidence: 65%
“…• Preloading the patients with crystalloids or colloids like albumin, 2 Hetastarch, 15,16 Dextran, 17 and polymerized gelatin before spinal anesthesia was found to be effective in reducing the incidence of hypotension. This study was conducted on 60 patients who came for elective cesarean section under spinal anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Vercauteren et al [19] studied 90 patients undergoing elective cesarean section under spinal anaesthesia who received ringer lactate (LR) 1000 ml with upto 1000 ml of modified gelatin, LR 1000 ml with upto 1000 ml of hydroxyethylstarch 6%(HES) or only upto 1000 ml of 6% HES. Lumbar puncture was performed as soon as 500 ml of the colloid was infused.…”
Section: Discussionmentioning
confidence: 99%